CREATIVE SPACE BAGI PENYANDANG GANGGUAN MENTAL DI BANJARBARU - Rachfa, Adhinda SafiraFaizatur; Muchammad, Bani Noor (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
Mental disorders are one of the social phenomena whose number is increasing every year. The increase in people with mental disorders is not accompanied by an increase in mental health facilities in Indonesia, especially in Banjarbaru. Creative Space for People with Mental Disorders in Banjarbaru is designed to be an alternative means of therapy and counseling for people with mental disorders through creative activities, with a behavior setting method that makes behavior the main focus in its design. And the concept of